Determinants of Youth Health Insurance Utilization in Eastern Indonesia: Evidence from the 2023 SUSENAS - Melly Cosmalinda Widyaningsih; Mahmudah Mahmudah; Devina Dwi Kurnia (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Youth, as a transitional age group, are often vulnerable to health problems yet tend to underutilize health services despite experiencing complaints. Health insurance plays a critical role in ensuring equitable access, especially in Eastern Indonesia where regional disparities persist. This study aimed to identify key factors influencing health insurance utilization among youth aged 15-24 years in East Nusa Tenggara, Maluku, and Papua Highlands. Methods: This cross-sectional study used data from the 2023 National Socioeconomic Survey (SUSENAS) conducted by Statistics Indonesia (BPS). Analysis included 2,649 youth aged 15-24 who reported health complaints in the previous month. Descriptive, bivariate, and multivariate logistic regression analyses were performed to determine the main predictors of health insurance utilization. Results: Although more than four-fifths of respondents were insured, only about one-fourth accessed health services. Regional disparities emerged as the strongest determinant of utilization. Youth in Maluku and East Nusa Tenggara were significantly less likely to be insured compared to their peers in Papua, while those living in rural areas showed higher odds of insurance use than those in urban settings. Individual characteristics such as age, gender, education, and employment status had minimal influence. Conclusion: Health insurance utilization among youth in Eastern Indonesia remains limited and largely shaped by structural and regional inequalities. Strengthening youth health literacy, simplifying insurance procedures, and improving service accessibility are essential steps toward equitable and youth-responsive universal health coverage in Indonesia and comparable middle-income settings.